Is early recurrence of hepatocellular carcinoma in HCV cirrhotic patients affected by treatment with direct‐acting antivirals? A prospective multicentre study. Issue 7 (9th August 2017) - Cabibbo, G.; Petta, S.; Calvaruso, V.; Cacciola, I.; Cannavò, M. R.; Madonia, S.; Distefano, M.; Larocca, L.; Prestileo, T.; Tinè, F.; Bertino, G.; Giannitrapani, L.; et al.
Summary: Background: Data on HCV‐related hepatocellular carcinoma (HCC) early recurrence in patients whose HCC was previously cured, and subsequently treated by direct‐acting antivirals (DAAs), are equivocal. Aim: To assess the risk of HCC early recurrence after DAAs exposure in a large prospective cohort of HCV‐cirrhotic patients with previous successfully treated HCC, also looking for risk factors for cancer early recurrence. Methods: We enrolled 143 consecutive patients with complete response after curative treatment of HCC, subsequently treated with DAAs and monitored by the web‐based RESIST‐HCV database. Clinical, biological, and virological data were collected. The primary endpoint was the probability of HCC early recurrence from DAA starting by Kaplan‐Meier method. Results: Eighty‐six per cent of patients were in Child‐Pugh class A and 76% of patients were BCLC A. Almost all patients (96%) achieved sustained virological response. Twenty‐four HCC recurrences were observed, with nodular or infiltrative pattern in 83% and 17% of patients, respectively. The 6‐, 12‐ and 18‐month HCC recurrence rates were 12%, 26.6% and 29.1%, respectively. Main tumour size and history of prior HCC recurrence were independent risk factors for HCC recurrence by Cox multivariate model. Conclusions: Probability of HCC early recurrence in patients who had HCC previously cured remains high, despite HCV eradication by DAAs. Risk was comparable but not higher to that reported in literature in DAA‐untreated patients. Previous HCC recurrence and tumour size can be used to stratify the risk of HCC early recurrence. Further studies are needed to assess impact of DAAs on late recurrence and mortality.